PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR - Septiana, Fera (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This main aims of this study is to test whether the companyâs characteristic which consists of profitability, type of industry, leverage, company size, company growth, foreign shareholder ownership, and size of board of directors affect the corporate social responsibility. The samples are manufacturing companies which are listed in Indonesia Stock Exchange in the year of 2010-2012. The samples have been selected by using purposive sampling method and 27 companies have been selected as samples. The data is the secondary data that is in the form of annual financial statement (annual report) and manufacturing companyâs financial statement which has been published. The results of this study show that: (1) profitability does not affect the corporate social responsibility, (2) the type of industry has no effect on the corporate social responsibility, (3) leverage has no effect on the corporate social responsibility, (4) the company size effect on the corporate social responsibility, (5) the company growth has no effect on the corporate social responsibility, (6) foreign shareholder ownership has no effect on the corporate social responsibility, (7) size of board of directors has no effect on the corporate social responsibilityKeywords: corporate social responsibility, profitability, leverage, companyâs characteristic.